Purification of an acidic coniferin-hydrolysing β-glucosidase from developing xylem of Pinus banksiana - Leinhos, Volker; Udagama-Randeniya, Preethi V.; Savidge, Rodney A. (Phytochemistry, 1994)
Two cytosolic, acidic (pI 3.8) glycoproteins (Mr 110 000 and 90 000) from lignifying xylem of Pinus banksiana were electrophoretically isolated and confirmed by combined gas chromatography-mass spectrometry to be capable of hydrolysing E-coniferin to trans-coniferyl alcohol. These isoenzymes yielded identical N-terminal sequences having negligible homology with documented glucosidases, suggesting that they constitute a novel form of β-glucosidase.
Keywords: Pinus banksiana; Gymnospermae; cambial growth; beta-glucosidase; lignin; secondary wall development; tracheary element differentiation; wood formation; xylogenesis